2002
DOI: 10.1046/j.1360-0443.2002.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of functional social support in treatment retention and outcomes among outpatient adult substance abusers

Abstract: Higher functional social support at intake is a positive predictor of retention in treatment, and a modest predictor of reductions in alcohol intake, but not in drug use. Overall, social support accounts for a small percentage of the variance in drug/alcohol-related outcomes, underscoring the need for further research into variables accounting for treatment success and failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
184
3
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(209 citation statements)
references
References 34 publications
15
184
3
7
Order By: Relevance
“…Specifically, the finding that individuals who lived alone, in a controlled, or in a nonstable living situation were less likely to enter treatment compared with those who lived with parents, family, children, or friends as well as a sexual partner might speak to the importance of social and emotional connections. This notion is supported by findings from prior studies in which emotional support has been found to be related to treatment retention (31). It is plausible that living arrangement might be an index of social support and social connectedness in this sample, which is an area for future research.…”
Section: Discussionsupporting
confidence: 73%
“…Specifically, the finding that individuals who lived alone, in a controlled, or in a nonstable living situation were less likely to enter treatment compared with those who lived with parents, family, children, or friends as well as a sexual partner might speak to the importance of social and emotional connections. This notion is supported by findings from prior studies in which emotional support has been found to be related to treatment retention (31). It is plausible that living arrangement might be an index of social support and social connectedness in this sample, which is an area for future research.…”
Section: Discussionsupporting
confidence: 73%
“…These protective effects are further documented in intervention studies with non-immigrants (Dobkin et al, 2002;Thompson et al, 2001), and while similar results can be observed with immigrant populations (Agudelo-Suarez et al, 2009;Noh & Kaspar, 2003), the effect is much more variable (Tsai & Thompson, 2013).…”
Section: Coping Resources and Mental Health Problemsmentioning
confidence: 79%
“…Individuals without strong and supportive networks of family and friends may be more likely to turn toward addictive behaviors and develop problems with them. Once problems with gambling or substances do develop, those with relatively stronger social support networks may be more likely to seek professional treatment early and benefit from it, as family and friends can be an important factor during the recovery process (1,(3)(4)(5). In contrast, those with poorer social support networks may have more severe problems, along with more pronounced difficulties along a number of dimensions (3,6).…”
Section: Introductionmentioning
confidence: 99%
“…Once problems with gambling or substances do develop, those with relatively stronger social support networks may be more likely to seek professional treatment early and benefit from it, as family and friends can be an important factor during the recovery process (1,(3)(4)(5). In contrast, those with poorer social support networks may have more severe problems, along with more pronounced difficulties along a number of dimensions (3,6). Poor social support may also be a factor in relapse, as negative affect (depressed mood, boredom) is a strong precipitant of gambling episodes among pathological gamblers seeking treatment (7,8) and among substance abusers (9).…”
Section: Introductionmentioning
confidence: 99%